2013
DOI: 10.25011/cim.v36i4.19954
|View full text |Cite
|
Sign up to set email alerts
|

Decreased plasma apolipoprotein A-IV levels in patients with acute coronary syndrome

Abstract: Purpose: The purpose of this study was to evaluate the relationship between apolipoprotein A-IV (apoA-IV) plasma concentrations and acute coronary syndrome (ACS). Methods: Plasma apoA-IV concentrations were measured in 115 patients with different types of ACS and in 68 gender- and age-matched control subjects using Enzyme-Linked Immunosorbent Assay (ELISA) kits. The clinical data were collected by an internist, who was blinded to plasma apoA-IV concentrations. Results: Plasma apoA-IV levels in ACS patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 36 publications
1
5
0
Order By: Relevance
“…It participates in reverse cholesterol transport 8 , 9 and plays an important role in relieving peripheral cells of an overload of cholesterol 10 , 11 . It has anti-atherogenic properties 12 , 13 and low concentrations were found to be associated with cardiovascular outcomes such as coronary heart disease or acute coronary syndrome 2 , 14 – 16 . About 30% of the phenotypic variance has been shown to be genetically regulated 17 .…”
Section: Introductionmentioning
confidence: 99%
“…It participates in reverse cholesterol transport 8 , 9 and plays an important role in relieving peripheral cells of an overload of cholesterol 10 , 11 . It has anti-atherogenic properties 12 , 13 and low concentrations were found to be associated with cardiovascular outcomes such as coronary heart disease or acute coronary syndrome 2 , 14 – 16 . About 30% of the phenotypic variance has been shown to be genetically regulated 17 .…”
Section: Introductionmentioning
confidence: 99%
“…Participants in previous studies were much older with the mean age above 60 years. 34,36 Thus, the present study might reflect the proteomic changes during AMI in younger populations that possibly associated with more significant inflammation reaction.…”
Section: Discussionmentioning
confidence: 81%
“…Chronic ingestion of high fat blunts the hypothalamic Apo A-IV response to lipid feeding and may explain why chronic intake of high fat predisposes animals and humans to obesity (38). Recently, low plasma Apo A-IV levels have been associated with acute coronary syndrome and plasma Apo A-IV levels have been proposed as a potential treatment target for patients with acute coronary syndrome (39). Guo et al (40) found Apo A-IV was correlated with the severity of obstructive sleep apnea-hypopnea syndrome.…”
Section: Discussionmentioning
confidence: 99%